2016
DOI: 10.1016/j.accfor.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of international financial reporting standards on the profit and equity of AIM listed companies in the UK

Abstract: This study examines the extent to which the change from UK GAAP to IFRS has affected companies listed on the Alternative Investment Market (AIM) in the UK. The results suggest that, on average, profit reported under IFRS is higher than that reported under UK GAAP; however, the difference is much smaller for AIM listed companies as compared to what existing literature suggests for firms listed on main stock markets. The Gray's partial analysis results indicate that despite the extensive programmes for improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
2
15
0
2
Order By: Relevance
“…In this case, the median value of 0.56 offers a better interpretation than the mean. This result is in line with recent studies by Ali, Akbar, and Ormrod (2016) that found a non-normal distribution of financial performance for AIM-listed firms in the UK and used the median for the interpretation of the descriptive statistics. The median value of 0.56, less than 1, indicates that the share prices of most AIM-listed firms were traded below £1.…”
Section: Presentation and Discussionsupporting
confidence: 91%
“…In this case, the median value of 0.56 offers a better interpretation than the mean. This result is in line with recent studies by Ali, Akbar, and Ormrod (2016) that found a non-normal distribution of financial performance for AIM-listed firms in the UK and used the median for the interpretation of the descriptive statistics. The median value of 0.56, less than 1, indicates that the share prices of most AIM-listed firms were traded below £1.…”
Section: Presentation and Discussionsupporting
confidence: 91%
“…Abdullah et al, 2015). Therefore, it is imperative for regulatory authorities to consider the fundamental elements of culture when adopting one size fits all reporting regime (Ali et al, 2016). Against this backdrop, it would make an intuitive sense to assume that differences in societies' value systems are likely to affect the acceptance and application of IFRS.…”
Section: The Role Of National Economic Culture Around Ifrs Adoptionmentioning
confidence: 99%
“…Consistent with previous IFRS research, we also build on positive accounting theory that was developed by Watts and Zimmerman (1986) to complement our understanding of the expected financial market consequences of ISAs adoption. According to positive accounting theory, financial markets are mostly enforced to adopt global accounting and auditing standards as a response to various stakeholders’ pressures, who seek to maximise their utility, which can often lead to unintended financial market consequences because of the inherent conflict of interests the exist between different stakeholders (Sayumwe and Francoeur, 2017; Senyiit, 2014; Samaha and Khlif, 2016; Ali et al , 2016; Ball, 2016; Kimeli, 2017; Kabir, 2010). The adoption of international accounting and auditing standards has both intended and unintended financial market consequences, which might either result in positive or negative effects on capital markets at the macro-economic level (Brüggemann et al , 2013).…”
Section: International Auditing Standards and Financial Market Indicatormentioning
confidence: 99%